CLEAN WATER PRODUCTION PERFORMANCE MEASUREMENT INDICATORS AND FACTORS: A REVIEW ON ULTRAFILTER MEMBRAN - M. Shahidul, Islam; Rubiyah, Baini; Shirley, Johnathan Tanjong; Ahmad, A.F; Hishammudin Afifi, Huspi (2023)
This review aims to answer the question relating to the problem of measuring the clean water production performance of the Ultrafilter membranes. This review has designed to study the research journal articles recently published (from 2000 to 2022) on the clean water production performance of ultrafilter membranes. The focus of this study was to unlock the influence of feed water quality, pre-treatment efficiency, Productivity, and energy consumption of the ultrafilter membrane on clean water production performance. The outcome of this review revealed that four indicators and thirteen potential factors have used for measuring the clean water production performance of ultrafilter membranes. The potential factors are the feed water pre-treatment, feed water pressure, chemically enhanced backwash, and osmotic pressure. Additionally, the pH, total suspended solids, turbidity, and chemical oxygen demand of feed water are the sources of cake layer formation that affect energy consumption and the operating cost of ultrafilter membranes in producing clean water. The findings of this review have a few industrial and policy implications. The outcomes of this review could be used by industrial engineers and consultants for designing the ultrafilter membrane system to optimize clean water production. The policy makers involved in technology selection for water filtration also can be used. The outcome of this study concludes that the ultrafilter membrane is an effective water treatment technology, but its performance depends on a few potential operating factors. This study recommends further research for optimizing the factors affect UFM performance in producing clean water